(untitled) (Experimental biology, 2015)
The raw materials choice for preparation of products (crispbread, biobread, a minus appetite) the increased nutritional value with treatment-and-prophylactic properties of a functional purpose – stevia leaves is reasonable. The technology of preparation of products is developed, the comparative characteristic organoleptic and some physics –chemical indicators of samples is carried out, optimum options of an additive are revealed.